Cognitive impairment and vulnerability of cholinergic brain network in the Alzheimer’s continuum: free-water imaging based on diffusion tensor imaging - Zhao, Simin; Nie, Yuting; Wen, Lulu; Qin, Xinzuo; Huang, Liyuan; Chu, Changbiao; Qu, Miao (Frontiers in Neuroscience, 2025)
BackgroundIncreased extracellular free water (FW) is considered to provide better pathophysiological information than conventional diffusion tensor imaging (DTI) metrics. The cholinergic brain network is a key hub for cognitive function, and microstructural changes detected by free water imaging in this system may be associated with cognitive impairment in Alzheimer’s disease (AD). However, the specific impact of FW changes in the cholinergic brain network on cognitive domains across the AD continuum and their diagnostic value remain unclear.MethodsHere, we investigated the basal forebrain cholinergic free water alterations based on free water-corrected diffusion tensor imaging in healthy controls (n = 36), amnestic mild cognitive impairment (aMCI; n = 31), the AD group (n = 33). The cholinergic basal forebrain subregions were divided into the Broca diagonal band (Ch1-3) and the Meynert basal nucleus (Ch4). The cognitive domains performance was measured using the Montreal Cognitive Assessment (MoCA). Additionally, we evaluated the diagnostic value of free water fraction (FWf) within the cholinergic system.ResultsFWf in the bilateral Ch1-3 and Ch4 regions increased with age, and was significantly higher in aMCI and AD (p < 0.001). In AD, the FWf within Ch4 was correlated with total MoCA score (R = −0.42, p = 0.015), especially with visual spatial/executive (R = −0.47, p = 0.006) and orientation deficits (R = −0.38, p = 0.029). No significant correlations were found in the aMCI group. ROC curve analysis showed that FWf within the cholinergic brain network had high diagnostic efficacy for AD versus HC (AUC = 0.958, 95% CI = 0.909–1.00), and moderate diagnostic efficacy for aMCI versus HC (AUC = 0.795, 95% CI = 0.685–0.905) and aMCI versus AD (AUC = 0.719, 95% CI = 0.589–0.850).ConclusionFW imaging captures microstructural damage in the cholinergic brain network across the entire AD continuum. These changes occur early in aMCI but selectively affect domain-specific cognition in the later stages of AD, possibly through cholinergic network dysfunction. Our results highlight the potential of free water imaging as a biomarker for cognitive decline.